Identification and Phenotype of MAIT Cells in Cattle and Their Response to Bacterial Infections - Edmans, Matthew D.; Connelley, Timothy K.; Jayaraman, Siddharth; Vrettou, Christina; Vordermeier, Martin; Mak, Jeffrey Y. W.; Liu, Ligong; Fairlie, David P.; Maze, Emmanuel Atangana; Chrun, Tiphany; Klenerman, Paul; Eckle, Sidonia B. G.; et al. (Frontiers in Immunology, 2021)
Mucosal-associated invariant T (MAIT) cells are a population of innate-like T cells that utilise a semi-invariant T cell receptor (TCR) α chain and are restricted by the highly conserved antigen presenting molecule MR1. MR1 presents microbial riboflavin biosynthesis derived metabolites produced by bacteria and fungi. Consistent with their ability to sense ligands derived from bacterial sources, MAIT cells have been associated with the immune response to a variety of bacterial infections, such as Mycobacterium spp., Salmonella spp. and Escherichia coli. To date, MAIT cells have been studied in humans, non-human primates and mice. However, they have only been putatively identified in cattle by PCR based methods; no phenotypic or functional analyses have been performed. Here, we identified a MAIT cell population in cattle utilising MR1 tetramers and high-throughput TCR sequencing. Phenotypic analysis of cattle MAIT cells revealed features highly analogous to those of MAIT cells in humans and mice, including expression of an orthologous TRAV1-TRAJ33 TCR α chain, an effector memory phenotype irrespective of tissue localisation, and expression of the transcription factors PLZF and EOMES. We determined the frequency of MAIT cells in peripheral blood and multiple tissues, finding that cattle MAIT cells are enriched in mucosal tissues as well as in the mesenteric lymph node. Cattle MAIT cells were responsive to stimulation by 5-OP-RU and riboflavin biosynthesis competent bacteria in vitro. Furthermore, MAIT cells in milk increased in frequency in cows with mastitis. Following challenge with virulent Mycobacterium bovis, a causative agent of bovine tuberculosis and a zoonosis, peripheral blood MAIT cells expressed higher levels of perforin. Thus MAIT cells are implicated in the immune response to two major bacterial infections in cattle. These data suggest that MAIT cells are functionally highly conserved and that cattle are an excellent large animal model to study the role of MAIT cells in important zoonotic infections.